Corrosion inhibition of mild steel by highly stable polydentate schiff base derived from 1,3- propanediamine in aqueous acidic solution - Noura H. Alharthi; Mohammed A. El-Hashemy; Wassila M. Derafa; Ibrahim O. Althobaiti; Hamud A. Altaleb (Journal of Saudi Chemical Society, 2022)
Recently, the hydrolysis of Schiff bases under experimental conditions gives suspicion for their corrosion inhibition performance. The current study employs a stable Schiff base namely, 2,2′-{propane-1,3-diylbis[azanylylidene (E) methanylylidene]}bis(6-methoxyphenol) (LPD) as corrosion inhibitor for mild steel (MS) in 1 M HCl solution. The presence of the characteristic peak of the imine group in UV-visible spectra was taken as an indicator for LPD stability in acidic media. The inhibition action was examined using electrochemical techniques including potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) besides gravimetric measurement. The inhibition efficiency reached 95.93 % for 0.75 mM LPD after 24 h of immersion at 25 °C. This high efficiency is owing to the presence of the characteristic imine group and other heteroatoms and π- electrons of the aromatic benzene rings. The mechanism of inhibition depends on adsorption phenomena on mild steel surface which obeys Langmuir isotherm model. The calculated values of adsorption equilibrium constant (Kads), adsorption free energy ΔGads, adsorption enthalpy ΔHads and adsorption entropy ΔSads indicated spontaneous exothermic adsorption process of both physical and chemical nature. By rising temperature, the inhibition efficiency of LPD was decreased. The calculated activation energy was increased as the concentration of LPD increased. LPD was considered as a mixed-type inhibitor as indicated from PDP measurements. The obtained surface morphology and composition analysis using SEM/EDS, AFM and FTIR techniques ensures the high efficiency of LPD as corrosion inhibitor.